2017
DOI: 10.1007/s40195-017-0630-3
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution and Growth Orientation of Directionally Solidified Mg–4 wt% Zn Alloy with Different Growth Rates

Abstract: The microstructure evolution and growth orientation of directionally solidified Mg-4 wt% Zn alloy in the growth rate range from 20 to 200 lm/s were investigated. A typical cellular structure was observed with a growth rate of 20 lm/s, and the cellular spacing was 115 lm. When the growth rate increased to 60 lm/s, cellular structure with some developed perturbations was obtained and the cellular spacing was 145 lm, suggesting that the cell-to-dendrite transition happened at the growth rate lower than 60 lm/s. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Yuan et al [15] processed hypereutectic Nb-Si alloys by directional solidification and have shown that the morphology of the cross section of eutectic cells changed from a square morphology to a nearly round morphology with increasing growth rate. Jia et al [16] used a Bridgman-type DS equipment to investigate the cellular/dendritic microstructural transition, which has been shown to occur for growth rates lower than 60 lm/s. Berkdemir and Gündüz [2] have analyzed Al-5 wt%Cu-(0.5-5) wt%Mg alloys grown in a Bridgman-type furnace at a constant G L equal to 4.84 ± 0.13 K/mm under different G R values varying from 16.7 to 83.3 lm/s.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al [15] processed hypereutectic Nb-Si alloys by directional solidification and have shown that the morphology of the cross section of eutectic cells changed from a square morphology to a nearly round morphology with increasing growth rate. Jia et al [16] used a Bridgman-type DS equipment to investigate the cellular/dendritic microstructural transition, which has been shown to occur for growth rates lower than 60 lm/s. Berkdemir and Gündüz [2] have analyzed Al-5 wt%Cu-(0.5-5) wt%Mg alloys grown in a Bridgman-type furnace at a constant G L equal to 4.84 ± 0.13 K/mm under different G R values varying from 16.7 to 83.3 lm/s.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mechanical and corrosion properties of magnesium alloys may be improved, which is attributed to this columnar structure [8,9]. Recently, the properties of DSed Mg-xZn alloys were studied by Jia et al [10,11], and the results indicate that the mechanical and corrosion properties of alloys with the columnar structure could satisfy the requirements of implant materials. So far, few researches have been conducted on the DSed Mg-Zn-Ca alloys for biodegradable materials.…”
Section: Introductionmentioning
confidence: 99%